Indonesian Language Politeness of Elementary Students at SDN 06 Kota Bengkulu - Daimun, Daimun; Novia, Novia (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
The purpose of this research was to describe Indonesian language politeness among the students, andbetween the students to their teachers at SDN 06 Kota Bengkulu. The subject of this research was thestudents at five grade. The scope of this research was the use of verbal and nonverbal politeness by thestudents and the teacher of SDN 06 Bengkulu: students with students, and students with teachers. Thistype of this research was qualitative descriptive. Data collected by observation, field notes, interviewtechniques and recording technique. Steps of data analysis conducted in stages, data reduction, datadisplay and data verification. The results of this research on linguistic politeness Indonesia students in theSDN 06 Kota Bengkulu, their are (1) for politeness the students data found conversional politenessstudents more than the data conversation violation of politeness, 21 data conversations containng maximsof politeness and 5 data conversation violation maxim of politeness, (2) for politeness between studentsand teachers found 7 data containing politeness conversation, and was not found students who violate themaxim of politeness and not found students against teachers. All data conversation concluded with a lookat the context of the speech that underline the conversation. The conclusion of this research was thepoliteness among the students and the students to their teacher reveal politeness. For nonverbal language,in students speaking use between body language and verbal language.